2013
DOI: 10.1177/0954407013495529
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new sound quality metric for evaluation of the interior noise in a passenger car using the logarithmic Mahalanobis distance

Abstract: Previous methods for the evaluation of the sound quality in vehicle interiors focused on the linear regression analysis of subjective sound quality metrics using statistics and estimations of subjective sound quality values by neural networks.Recently, sound quality evaluation using subjective measures has focused on identifying sound quality metrics which can predict subjective responses. It has been used to study a variety of subjective measures such as the four parameters used by Zwicker, but it is difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Jeong, JE. et al [ 12 ] suggested a new evaluation index based on the Mahala-nobis distance using four parameters Zwicker employed to estimate the subjective perception of sound quality. Through a correlation analysis with jury tests, it was found that the logarithmic Mahala-nobis distance can serve not only as a novel index but also as a reliable criterion for evaluating.…”
Section: Introductionmentioning
confidence: 99%
“…Jeong, JE. et al [ 12 ] suggested a new evaluation index based on the Mahala-nobis distance using four parameters Zwicker employed to estimate the subjective perception of sound quality. Through a correlation analysis with jury tests, it was found that the logarithmic Mahala-nobis distance can serve not only as a novel index but also as a reliable criterion for evaluating.…”
Section: Introductionmentioning
confidence: 99%
“…Seo et al 12 developed an improved sound quality evaluation scheme that was applicable to mono-channel characterization and multichannel characterization of signals, taking both ''spatial'' and ''timbral'' characteristics into account, and that is important for testing the quality of multichannel sound. Jeong et al 13 developed a new sound quality index that took four parameters used by Zwicker, and that received Mahalanobis distance as the basis to project the results of subjective evaluation of sound quality. It has been demonstrated that the log Mahalanobis distance was a new sound quality index employed for the assessment of vehicle performance.…”
Section: Introductionmentioning
confidence: 99%